The reliability and reproducibility of sagittal spinal curvature measurement using the Microsoft Kinect V2 - Hannink, E; Shannon, T; Barker, K; Dawes, H (IOS Press, 2019)
BACKGROUND:Abnormal sagittal spinal curvature is associated with pain, decreased mobility, respiratory problems and increased mortality. Time-of-flight technology of the Microsoft Kinect sensor can reconstruct a three-dimensional image of the back quickly and inexpensively. OBJECTIVE:To estimate the extent of the reproducibility of sagittal spine curvature measurement using the Microsoft Kinect sensor. METHODS:Simultaneous measurement of thoracic and lumbar spine using the Microsoft Kinect sensor in 37 participants. Two investigators gave standardised instructions and each captured 3 images. Thoracic kyphosis and lumbar lordosis angle indexes were calculated using maximum height divided by the length. RESULTS:Adult participants (mean age in years (SD) = 51.7 (20.6); 57% female; BMI in kg/m2 (SD) = 24.9 (3.3)) kyphosis and lordosis indexes showed high intra-rater and inter-rater ICC values (0.960-0.973). The means of the first images from both raters had significantly larger kyphosis indexes compared to the second and third images, yet no difference between means in lordosis data. CONCLUSIONS:The results indicate that the Microsoft Kinect sensor has a reproducible method with high intra-rater and inter-rater reliability. The difference between the means over repeated measures suggest the second image capture is more consistent. It is a reproducible and quick method in clinical and research settings.